Immediate and delayed allergy from epoxy resins based on diglycidyl ether of bisphenol A. - Kanerva, L; Jolanki, Riitta; Tupasela, O; Halmepuro, L; Keskinen, Helena; Estlander, T; Sysilampi, M L (Scandinavian Journal of Work, Environment & Health, 1991)
This case report presents two patients with immediate and delayed allergy to epoxy resins based on diglycidyl ether of bisphenol A (DGEBA). In patch testing, the epoxy resin (DGEBA-based) of the standard series gave allergic reactions. Both patients had a prick test reaction of histamine size or larger to the human serum albumin (HSA) conjugate of DGEBA-based epoxy resins. One had been occupationally exposed to methyl tetrahydrophthalic anhydride (MTHPA) and had a histamine-size prick test reaction to the HSA conjugate of MTHPA; the other did not react to the conjugate. Determinations of specific immunoglobulin E were carried out with HSA-DGEBA conjugates, two DGEBA-based epoxy resins, and phthalic anhydrides. The first patient had positive tests to DGEBA, the DGEBA-based epoxy resins, and two phthalic anhydrides, and the second to DGEBA and the DGEBA-based epoxy resins, but not to the phthalic anhydrides.